- Resepsi Content Creator dalam Institusionalisasi Dakwah Digital: Studi Kasus Produksi Konten TikTok Bedaie Official - Hasna Zahra Annabilah; Tata Sukayat; Prita Priantini Nur Chidayah (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2026)
This study investigates how content creators in Bedaie Official's institutionalized digital da'wah receive, interpret, and renegotiate institutional messages in the production of TikTok content. Drawing on Stuart Hall's encoding-decoding framework, the research examines three creators, Meriana Tri Wahyuni, Amaniatul Bahriah, and Ade Fauziah, who occupy distinct but interrelated positions within the production chain. Using qualitative case study design, data were gathered through semi-structured interviews, participatory observation of virtual coordination spaces, and digital document analysis, including scripts, KPI spreadsheets, production notes, and published videos. The findings reveal a trajectory from strict central standardization, requiring creators to mirror Malaysian reference formats in script, speech, gesture, and editing, toward directed improvisation, in which language, visual framing, and hook design are adapted for Indonesian TikTok audiences while fiqh boundaries remain intact. The study proposes the concept of productive decoding to capture the dual position of creators as both decoders of institutional religious messages and re-encoders for platform audiences, extending reception theory beyond end-users toward the creative intermediaries who mediate between religious authority and algorithmic visibility.